Do behavioural inattention and hyperactivity exacerbate cognitive difficulties associated with autistic symptoms? Longitudinal profiles in fragile X syndrome. (1st July 2013) - Cornish, Kim; Cole, Victoria; Longhi, Elena; Karmiloff-Smith, Annette; Scerif, Gaia
<x xml:space="preserve">Abstract</x> Developmental trajectories of autism spectrum disorder (ASD) or attention deficit and hyperactivity disorder (ADHD) comorbidity in genetically determined neurodevelopmental disorders are not well understood. The objective of the current longitudinal study was to explore symptomology and comorbidity in boys with fragile X syndrome focusing on their profiles of autistic and inattentive behaviours in performance on the Leiter R Performance Scale, a non-verbal IQ measure. Of the 46 children, 10 were classified as having combined ASD and ADHD symptoms, 14 met the criterion for autism alone, 10 met the criterion for ADHD alone, and 12 had no symptoms for either. Results indicated that changes in cognitive profiles over time were similar for all groups and there was a slight improvement in growth scores suggesting developmental change. In terms of ASD and ADHD symptomology, we also found stable differences across groups over time. Collectively, these findings highlight the pressing need to explore symptomology longitudinally across disorders at high risk from comorbid ASD and ADHD diagnoses.